Development of semiconductor lasers emitting in the visible (0.6 um) to mid-infrared (2.6 um) regions - Chan, Yuen Chuen (2008)
The project established the basic technologies in the development of the semiconductor laser diode in NTU. The scope includes epitaxial growth, laser device processing, as well as laser performance characterization and analysis.